Effect of the surface chemical treatment on the properties of a sol–gel film on AA1050. (16th September 2015) - Deflorian, F.; Fedel, M.
Abstract : Silane sol–gel coatings have been widely studied as a potential strategy to protect aluminium and aluminium alloys components and were proved to be suitable both as a chemical conversion treatment alone and as a coupling agent between the underling substrate and an organic coating. Compared with many aluminium alloys, only little investigation was carried out on the application of sol–gel coatings on AA1XXX. Despite pure aluminium shows lower mechanical resistance with respect to aluminium alloys, however, the high thermal conductivity makes it suitable in a huge variety of applications, such as heat exchanger constructions as well as cooling systems. The present work is devoted to the study of the effect of the surface chemical pretreatment on the structural and corrosion protection properties of a hybrid sol–gel film. Different surface chemical treatments of the 1050 aluminium alloy prior sol–gel deposition were tested: alkaline etch, acidic passivation and boiling water immersion (to promote the formation of pseudo‐boehmite). Films of 1 :1 molar ratio of GLYMO : MTES were obtained on AA1050 from a 5wt% solution in acidified water. The effect of the chemical surface treatment on the AA1050 substrate was investigated both in terms of morphology by means of scanning electron microscopy and in terms of surface chemistry by means of Fourier Transform Infrared Spectroscopy (FT‐IR) exploiting attenuated total reflectance (ATR) geometry. The structure and the chemical properties of the different coatings were investigated by means of FT‐IR. The characterization of the different protective coatings was carried out by means of electrochemical impedance spectroscopy measurements and potentiodynamic curves. Copyright © 2015 John Wiley & Sons, Ltd.